Desenvolvimento de um circuito conversor CC-CC para o acionamento de lâmpada LED para iluminação interior - Kava, Murilo Dingueleski (2019)
This work presents the study of DC-DC converter circuits for the operation of residencial LED bulbs, as well as the simulation and implementation of a laboratory prototype. Inicially, are presented the advantages of the LED lighting and after are presented the power converters with some of the more simple topologies, with the simulation of the buck, bock-boost and flyback converters operating in the discontinuous current mode. After the simulations, it is choosen to implement a laboratory prototype of a flyback converter due it’s better project flexibility, isolation and the possibility to supply more than one load. The project and implementation of the prototype are realized, as well as the admeasurement and discussion of the results, presenting the ways the prototype can be improved.